ASSOCIATION BETWEEN TNF-Α-308 G/A GENE POLYMORPHISM AND GASTRIC CANCER RISK - Архипова, Анна Александровна; Анищенко, Владимир Владимирович (Medicine in Kuzbass, 2020)
Subject of research. Venous blood of patients with gastric cancer hospitalized with gastrointestinal bleeding. The study group included 14 men (45 %), 17 women (55 %), average age 63.2 ± 3.5 (M ± m). The comparison group included 58 patients undergoing medical examination prior to surgical treatment (replacement arthroplasty). Gender distribution of the patients in the comparison group – 19 men (33 %), 39 women (67 %), average age 62.4 ± 1.8 (M ± m) Objective – to determine the risk of development of gastric cancer based on the analysis of polymorphism of tumor necrosis factor alpha. Research methods. DNA isolation was performed using phenol-chloroform extraction. Genotyping of single nucleotide substitutions in the TNF-α gene at -308 (G; A) was performed using real-time PCR with competitive TaqMan probes complementary to polymorphic DNA regions. The accuracy of the genotyping is confirmed by sequencing. Key findings. The distribution of TNF-α genotypes at -308 (G; A): GG 58 %, GA 42 % and AA 0 % in patients with gastric cancer and GG 79 %, GA 21 % and AA 0 % in the comparison group. In the group of patients with cancer the heterozygous GA genotype of the TNF-a gene was more frequent than in the comparison group: 42 % versus 21 % (χ2 = 4.514; р = 0,034). Calculation of odds ratio has shown that the GA genotype is associated with risk of gastric cancer development (OR = 2.769; lower limit 95% CI = 1.065, upper limit 95% CI = 7.197). Scope of application. Formation of gastric cancer development risk groups. Conclusions. The results of our study demonstrate the association between the heterozygous GA TNF-a-308 genotype and the risk of development of gastric cancer.